Experimental investigations of kerosene sprays in pressurized evaporating environments. (May 2019) - Liu, Tao; Fu, Wei; Yi, Bolun; Song, Lanbo; Lin, Qizhao; Zhao, Dongmei
Experiments of kerosene spray with single-hole solenoid injector in the pressurized nonevaporating and evaporating environments, in which the ambient pressure ranges from 1.4 MPa to 4.8 MPa and the ambient temperature includes 300 K, 343 K, and 423 K, are carried out with high-speed Schlieren photography to investigate the breakup regimes and the macro-characteristics like penetration, projected spray area, and spray cone angle. Repetitive experiments are conducted to analyze the penetration repeatability. The comparison between the experimental penetrations and the predicted ones by the existing correlations reveals that the deviations between the experimental data and the predictions rise as the ambient temperature rises. Therefore, a new modified correlation is proposed to predict the penetration of kerosene spray in the nonevaporating and evaporating environments, which fits the experimental data better than the existing correlations. The breakup regimes in primary breakup and secondary breakup are discussed respectively. The projected spray area is analyzed under different ambient pressures at different ambient temperatures. Finally, it is found that the spray cone angle remains almost the same under different ambient pressures after it reduces sharply before 0.5 ms. The macro-characteristics discussed in the present study are important for the performance and emissions of aeronautical engines or diesel engines fuelled by kerosene as a substitution.